Effectiveness of subspinal Le Fort I osteotomy in preventing postoperative nasal deformation. Issue 7 (July 2020) - Yamashsita, Yosuke; Iwai, Toshinori; Honda, Koji; Fujita, Koichi; Imai, Haruki; Takasu, Hikaru; Omura, Susumu; Hirota, Makoto; Mitsudo, Kenji
Summary: Purpose: This study sought to determine the effectiveness of subspinal Le Fort I osteotomy (SLFIO) in preventing nasal deformation, by analyzing changes in the nasal profile on three-dimensional computed tomography (3D-CT) images. Patients and methods: The participants were 39 Japanese patients with mandibular prognathism (6 men and 33 women) who underwent bilateral sagittal split ramus osteotomy and Le Fort I osteotomy with maxillary advancement: SLFIO was performed in 20 patients and conventional Le Fort I osteotomy (CLFIO) in 19 patients. All patients underwent modified alar base cinch suture, V-Y closure, and reduction of the piriform aperture. CT data acquired before and 1 year after the surgery were evaluated three-dimensionally with software to determine changes in the nasal profile. Results: Changes in alar width, alar base width, nasal length, and nasofrontal angle were significantly smaller following SLFIO than following CLFIO, although there were no significant differences in nasal projection, nasal tip angle, or nasolabial angle between two procedures. Conclusion: SLFIO for anterior repositioning of the maxilla can prevent undesirable transverse soft tissue changes of the nose.